A Phoenician glass eye bead from 7th–5th c. cal BCE Nin-Bèrè 3, Mali: Compositional characterisation by LA–ICP–MS. (April 2019) - Truffa Giachet, Miriam; Gratuze, Bernard; Ozainne, Sylvain; Mayor, Anne; Huysecom, Eric
Abstract: The so-called Phoenician or Punic eye beads are a well-known type of glass artefacts circulating all over the Mediterranean Basin and Europe for most of the 1st millennium BCE. Glass beads were mostly produced in secondary workshops from imported raw glass or recycled artefacts but the specific sites of manufacture remain difficult to locate. Nevertheless, numerous chemical studies of glass from the area of interest proved that natron -based soda-lime-silica glass was the most widespread from 10th–9th century BCE to 8th–9th century CE. A glass eye bead typologically consistent with the Phoenician ones was unearthed during the archaeological excavation of the Nin-Bèrè 3 settlement site in Mali in a context dating between the 7th and the 5th centuries cal BCE. The chemical analysis by means of Laser Ablation – Inductively Coupled Plasma – Mass Spectrometry (LA–ICP–MS) has been carried out in order to confirm the characteristic composition of Mediterranean Iron Age glass. Results show the bead to be soda-lime silica glass fluxed with mineral soda, and coloured and opacified with cobalt, copper, and antimony. The minor and trace elements are also consistent with said composition. This exceptional find this far south expands greatly the area of distribution of these artefacts and it suggests a very early indirect contact between sub-Saharan Africa and the Mediterranean Basin. At the current state of research, this is the most ancient glass bead found south of the Sahara desert. Highlights: A glass eye bead fragment was found in 7th to 5th century BCE Nin-Bèrè3 site in Mali. Oldest glass item found in securely dated sub-Saharan African archaeological site. Typology matches the glass eye beads traded by Phoenicians in Mediterranean basin. Chemical analysis confirms the typical contemporary Mediterranean glass composition. Exceptional find attests earliest trade between West Africa and Mediterranean world.